1992
DOI: 10.1016/0014-5793(92)80369-r
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐bound annexin V isoforms (CaBP33 and CaBP37) and annexin VI in bovine tissues behave like integral membrane proteins

Abstract: The distribution of annexin V isoforms (CaBP33 and CaBP37) and of annexin VI in bovine lung, heart, and brain subfractions was investigated with special reference lo the fractions of these proteins which are membrane.bound. In addition to EGTA.extmetable pools of the above proteins, membranes from lung, heart, and brain contain EGTA-resistant annexins V and VI which can be solubilizcd whh detergents (Triton X-100 or Triton X-114). A strong base like Na:CO~, which is usually effective in extracting peripheral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
22
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 41 publications
8
22
0
Order By: Relevance
“…In addition, subcellular fractionation studies have shown that in heart, lung, liver, platelets and brain a proportion of the total annexin V remains associated with membranes even after extraction with EGTA. It is therefore likely that annexin V plays a role in the regulation of a membranelocalized process [7,8,[25][26][27][28]. We have demonstrated that, following physiological platelet activation, annexin V relocates from the cytosol and binds to membranes, which implicates annexin V in coupling increases in cytosolic [Ca# + ] to membranespecific processes [7,8].…”
Section: Introductionmentioning
confidence: 79%
“…In addition, subcellular fractionation studies have shown that in heart, lung, liver, platelets and brain a proportion of the total annexin V remains associated with membranes even after extraction with EGTA. It is therefore likely that annexin V plays a role in the regulation of a membranelocalized process [7,8,[25][26][27][28]. We have demonstrated that, following physiological platelet activation, annexin V relocates from the cytosol and binds to membranes, which implicates annexin V in coupling increases in cytosolic [Ca# + ] to membranespecific processes [7,8].…”
Section: Introductionmentioning
confidence: 79%
“…The cruvirus-binding protein we found probably corresponds to ancial question is whether binding of influenza virus to annexin nexin V. Further experiments showed that infection of influ-V (or annexin 33 kDa) is an essential step for infection. Anenza viruses could be inhibited by externally added phosphonexins are thought to be both intracellular and plasma memlipids as well as by antiserum against annexin V. These results brane components [10][11][12]. If the binding of viral phospholisubstantiated our view that annexins may serve as a second pids to the annexins of the plasma membrane is an essential receptor for these viruses, step for infection, externally added phospholipids should compete in this reaction, resulting in the inhibition of virus infec-2.…”
mentioning
confidence: 87%
“…brane components [10][11][12]. To test the effect of anti-annexin V antiserum on virus multiplication, it was added to cells before viruses were given and the cells were maintained in the constant presence of this antiserum.…”
Section: Culture Cell Viruses and Annexin Vmentioning
confidence: 99%
“…Both Anx2 and Anx5 are widely expressed, although Anx5 expression is particularly prominent in skeletal, cardiac, and smooth muscle, Leydig cells, endothelia, chondrocytes, and some neurons (3)(4)(5)(6)(7)(8). Like many annexins, Anx2 and Anx5 are predominantly intracellular, existing both as soluble cytosolic proteins and also in Ca 2ϩ -dependent and Ca 2ϩ -independent association with a range of intracellular membranes (9)(10)(11)(12), including the plasma membrane and early endosomes (13,14). However, only Anx5 has been associated with late endosomes and mitochondria (15).…”
mentioning
confidence: 99%